Comparison of the Effectiveness of Acceptance and Commitment Therapy and Reality Therapy in Reducing Depression and Anxiety in Families of COVID-19 Victims - Asgharyar, Mohsen; Jajarami, Mahmoud; Bakhshipour, Abolfazl (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: The present study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Reality Therapy in reducing depression and anxiety in families of COVID-19 victims. Methods and Materials: The research method was a quasi-experimental design with a pre-test and post-test with a control group, along with a three-month follow-up. The sample consisted of 45 individuals from families of COVID-19 victims, who were randomly assigned to two experimental groups and one control group (15 participants in each group). The two experimental groups received therapy in eight weekly sessions, each lasting 90 minutes. No intervention was provided to the control group. Participants completed the DASS21 questionnaire (1995) at three points: pre-test, post-test, and follow-up. The collected data were analyzed using inferential statistics (repeated measures analysis of covariance) in SPSS version 24. Findings: The results showed that, in both experimental groups, the mean scores of depression and anxiety variables were higher at the post-test and follow-up stages compared to the pre-test stage. Furthermore, it was observed that the post-test mean score of the ACT group did not significantly differ from the Reality Therapy group in terms of depression and anxiety at the follow-up stage. Conclusion: Based on the findings, it was concluded that both therapies were effective in reducing depression and anxiety.